Breast reconstruction patterns and outcomes in academic and community practices within a single institution. Issue 5 (1st December 2019) - Gabrick, Kyle; Alperovich, Michael; Chouari, Fouad; Mets, Elbert J; Reinhart, Manuel; Dinis, Jacob; Avraham, Tomer
Abstract: Breast reconstruction is a common procedure that is performed in both community and academic settings. At Yale‐New Haven Hospital (YNHH), both academic (AP) and community‐based (CP) plastic surgeons perform breast reconstructions. We aim to compare practice patterns in breast reconstruction between two practice environments within a single institution. A retrospective chart review of all breast reconstructions at YNHH between 2013 and 2018 was performed. Data collected included demographics, preoperative history, and postoperative outcomes. Results were further subdivided by practice setting. A total of 1045 patients (1683 breasts) underwent breast reconstruction during the study period. About 52.8% were performed by AP while 47.2% were performed by CP. CP had higher rates of autologous reconstruction ( P < .001) and nipple‐sparing mastectomy ( P < .0001). Age and BMI were similar between the cohorts. However, patients cared for by AP had 2.6% increased prevalence of diabetes ( P = .064), 5.5% greater prevalence of psychiatric diagnoses ( P = .004), and 7.1% higher open abdominal surgery rates ( P < .001). Outcomes were similar between the groups except for higher infection rates ( P = .027) and explant rates ( P = .003) in the CP cohort. When evaluating insurance status, the AP cohort had 30.5% fewer patients with commercial insurance, 16.7% more patients with Medicaid and 6.1% more patients with Medicare ( P < .001). Within our institution, academic and community‐based plastic surgeons perform breast reconstruction with overall similar complication rates. Patients treated by AP have a higher rate of preoperative medical and psychiatric comorbidities. Patients treated by CP have higher rates of infection and implant explant. AP plastic surgeons care for a significantly higher rate of Medicare and Medicaid patients with proportionally fewer patients with commercial insurance.